2018
DOI: 10.1002/cncr.31787
|View full text |Cite
|
Sign up to set email alerts
|

Role of adjuvant therapy in resected stage IA subcentimeter (T1a/T1b) pancreatic cancer

Abstract: Objectives: Standard of care treatment for resected stage I-III pancreatic ductal adenocarcinoma (PDAC) is adjuvant gemcitabine-based chemotherapy. The role of adjuvant treatment for sub-centimeter, stage IA PDAC is unknown. This study evaluated the effect of adjuvant treatment on survival outcomes of stage IA (T1N0), resected PDAC using the National Cancer Database (NCDB). Methods: Retrospective review of the NCDB was conducted for T1 (tumor limited to pancreas, ≤2 cm in greatest dimension), node negative (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…The current recommendation is that MCN‐AIC patients follow the standardized chemotherapy‐based management applied in treating conventional pancreatic cancer [ 30 , 31 ]. Recently, a retrospective analysis suggested that, for early‐stage PDAC patients with carcinoma measuring <1 cm (T1a/T1b), survival is not significantly different between patients who received adjuvant treatment and those who did not [ 32 ]. As for MCN‐AICs, Hui et al [ 4 ] presented three well‐documented T1a/T1b MCN‐AICs with favorable prognosis and advocated for regular follow‐up to reduce the use of systemic chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The current recommendation is that MCN‐AIC patients follow the standardized chemotherapy‐based management applied in treating conventional pancreatic cancer [ 30 , 31 ]. Recently, a retrospective analysis suggested that, for early‐stage PDAC patients with carcinoma measuring <1 cm (T1a/T1b), survival is not significantly different between patients who received adjuvant treatment and those who did not [ 32 ]. As for MCN‐AICs, Hui et al [ 4 ] presented three well‐documented T1a/T1b MCN‐AICs with favorable prognosis and advocated for regular follow‐up to reduce the use of systemic chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…According to the 7th edition AJCC staging manual, Ostapoff et al (25) showed that adjuvant chemotherapy was associated with better OS outcomes for stage I PDAC (including stage IA and IB) using the National Cancer Data Base (NCDB). Also using the NCDB, however, Shaib et al (26) further reported that adjuvant chemotherapy did not improve the prognosis for stage I sub-centimeter PDAC (<1 cm in greatest dimension). Although the classification methods in our study varied from the previous studies, these results indicated that early-stage PDAC patients may not benefit from adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperatively, however, less than 50% of patients received adjuvant chemotherapy [38] . In a retrospective study of PDAC, Shaib W.L et al had reported that the adjuvant chemotherapy could prolong survival time [39] . In the same study, Nagrial A.M et al had reported that the elder PDAC patients who had received postoperative adjuvant chemotherapy could live longer [40] .…”
Section: Discussionmentioning
confidence: 99%